USULAN RENCANA PERBAIKAN KUALITAS PRODUK KOMPONEN VAMP DENGAN PENDEKATAN METODE GEMBA KAIZEN (5W+2H) DI PT. MASTERINA GRAFIKA ESPRINTA - Ekky Handoko; Wirawati, Sri Mukti; Gunawan, Wawan (Journal of Industrial Engineering & Management Research, 2020)
Increasing productivity is very important for companies to get success in business processes. Masterina Grafika Esprinta, Ltd is an industrial company engaged in printing sport shoes upper, which was founded in 1984, the upper part of which is printed including Vamp, Tongue, Heel, Collar, Eyestey, and Quarter. This study aims to determine the causes of defects in the vamp component production process using gemba kaizen method that refers to the concept of PDCA (plan, do, check, action), 5W + 2H, 5S. Based on data processing and analysis results during research, the conclusions obtained are as follows: Results of research identification based on production data during the January 2019 - December 2019 period are the total production of vamp components of Masterina Grafika Esprinta, Ltd is 1132525 pairs. The types of defects that have the highest frequency of the vamp component production process are ink defects widened out of the pattern with total defects reaching 10392 pairs or around 55,8% of total defects (18624 pairs), and gross surface defects with total defects reaching 8043 pairs or around 43,19% of the total defects (18624 pairs). Judging from the problems that occur, the kaizen method is a method of improvement that is carried out continuously to achieve better results, and several important roles at the time of improvement, namely the role of top management, supervisors and employees must be performed.